The combined effect of fire and nitrogen addition on biodiversity and herbaceous aboveground productivity in a coastal shrubland - Qi, Luyu; Song, Yixin; Zhang, Puyi; Sun, Wenlong; Wang, Wei; Yi, Shijie; Li, Jing; Liu, Haifang; Bi, Zhenggang; Du, Ning; Guo, Weihua (Frontiers in Plant Science, 2023)
Introduction: Fire and nitrogen (N) deposition each impact biodiversity and ecosystem productivity. However, the effect of N deposition on ecosystem recovery after fire is still far from understood, especially in coastal wetlands.We selected a typical coastal shrubland to simulate three N deposition levels (0, 10, 20 g N m -2 year -1 ) under two different burned conditions (unburned and burned) in the Yellow River Delta of North China. Soil properties, soil microbial biodiversity, shrub growth parameters, herbaceous biodiversity and aboveground productivity were determined after experimental treatments for one year.Results: We found that fire had a stronger influence on the ecosystem than N addition.One year after fire, shrub growth had significantly decreased, while soil pH, soil electrical conductivity, herbaceous biodiversity, soil microbial biodiversity and herbaceous aboveground productivity significantly increased. Conversely, a single year of N addition only slightly increased herbaceous aboveground productivity. The combined effect of fire and N addition was only significant for fungus biodiversity, and otherwise had minimum influence. Interestingly, we found that herbaceous aboveground productivity was positively associated with fungal community diversity under unburned condition, but not in burned shrublands. Fire showed great impact on soil parameters and biodiversity in the coastal wetland ecosystem even after a full year of recovery.Discussion: Fire may also diminish the influence of several belowground factors on herbaceous aboveground productivity, which ultimately reduce recovery and stability.Appropriate N addition may be an effective way to improve the ecosystem productivity in the wetland dominant by shrub species.